Difficulties Face Students In Writing a Research Project - Wali, Nizar Hussein (Journal of Tikrit University for Humanities, 2024)
Writing a Research is a serious and challenging mission requires an accepted knowledge of the subject matter .It is considered as a graduation research for students in the final year of studying at most of the college level . Writing a research needs careful planning and hard working in order to finish the task successfully. This study is an attempt to find out the challenges and difficulties that face students in writing a research graduation project. The sample of the study is (120 ) students (60 male and 60 female ) which represents the fourth stage of students at English Department - College of Basic Education -Diyala University during the academic year 2022-2023. The study includes a questionnaire and informal interview with students of the target groups to gain information related to the aims of the study . Clearly, the results of the study showed that the participants face challenges and difficulties in writing a research project. The study explored a number of these challenges during writing the research project as misunderstanding the exact scope of the topic for the suggested title, lack of knowledge about the suggested topic, weakness in the methods of research as a guide for research writing, difficulty in searching for related references ,the absence of interest in writing a research and difficulty in understanding of the whole subject matter. The study ends up with some suggestions and recommendations which may help students for improving the process of writing research project.